THE EFFORTS OF AKIDAH AKHLAK TEACHERS IN PREVENTING BULLYING BEHAVIOUR AT MADRASAH TSANAWIYAH NEGERI 3 JAMBI CITY - Wildan Mukholid; Khoirul Anwar (Universitas Nias Raya, 2026)
This study aims to describe the forms of bullying behaviour, the obstacles encountered, and the efforts of Akidah Akhlak teachers in preventing bullying at Madrasah Tsanawiyah Negeri 3 Jambi City. A qualitative approach with a case study design was employed. Data were collected through observation, in-depth interviews, and documentation involving the school principal, Akidah Akhlak teachers, and students of Class XII B. Data analysis followed Miles and Huberman's interactive model, whilst trustworthiness was established through triangulation, persistent observation, and extended engagement. The findings reveal that bullying manifests in three forms: verbal, social, and physical, with verbal bullying being most prevalent. Key obstacles include limited instructional time, insufficient staff coordination, adverse family environments, and negative media influence. The teacher's preventive efforts encompass values-based instruction, empathy cultivation, individual counselling, disciplinary enforcement, and parental collaboration. These findings affirm the central role of Islamic moral education in addressing bullying within the madrasah setting.